An Analysis of Educational Value in "Freedom Writers" Movie By Richard LaGravenese - Nayanti, Eki; Aderlaepe, Aderlaepe; Alberth, Alberth (Journal of Teaching English, 2019)
This research was accomplished to find out the Educational Values which were consisted in Freedom Writers movie and provide detail information about the educational value of the movie. The problem of this research was what is the educational value in the Freedom Writers movie. The objective of the research was to describe and analyze the educational values in the â€œFreedom Writersâ€ movie. The data sources were collected from the script of the movie that was written by Richard Lagravenese. The researcher used qualitative analysis as her research design. The source of data can be divided into two kinds: primary and secondary data. The primary data sources were the script movie of â€œFreedom writersâ€ Movie that was written by Richard LaGravenes and set in 2007. The secondary data was â€œFreedom Writersâ€ movie. The researcher collected the data by doing some underlining of the script which was related to educational value and then making a classification of data. In analyzing the data, there are some procedures as follows: firstly: the researcher was familiar with the data through read the whole material as the first activity, secondly coding and reducing process and thirdly, Interpretation and representing, In this technique, the writer tried to understand the meaning of the sentences or words that related to the educational values. When interpretation was on process, the researcher also concluded the data based on the code that has been given in order to answer the problem statement. This research also used descriptive analysis in analyzing the educational value to report clear information. The result confirmed that there were four value of being and five value of giving namely honesty, bravery, peace, confidence, loyalty, respect, love, and affection, kind and friendly and fair which had been found by the researcher. It was recommended to the next researcher who wants to conduct some research to found out more value which might be the weakness of this research.